The Abundance of Endofungal Bacterium Rhizobium radiobacter (syn. Agrobacterium tumefaciens) Increases in Its Fungal Host Piriformospora indica during the Tripartite Sebacinalean Symbiosis with Higher Plants - Guo, Huijuan; Glaeser, Stefanie P.; Alabid, Ibrahim; Imani, Jafargholi; Haghighi, Hossein; Kämpfer, Peter; Kogel, Karl-Heinz (Frontiers in Microbiology, 2017)
Rhizobium radiobacter (syn. Agrobacterium tumefaciens, syn. “Agrobacterium fabrum”) is an endofungal bacterium of the fungal mutualist Piriformospora (syn. Serendipita) indica (Basidiomycota), which together form a tripartite Sebacinalean symbiosis with a broad range of plants. R. radiobacter strain F4 (RrF4), isolated from P. indica DSM 11827, induces growth promotion and systemic resistance in cereal crops, including barley and wheat, suggesting that R. radiobacter contributes to a successful symbiosis. Here, we studied the impact of endobacteria on the morphology and the beneficial activity of P. indica during interactions with plants. Low numbers of endobacteria were detected in the axenically grown P. indica, (long term lab-cultured, lcPiri) whereas mycelia colonizing the plant root contained increased numbers of bacteria. Higher numbers of endobacteria were also found in axenic cultures of P. indica that was freshly re-isolated (riPiri) from plant roots, though numbers dropped during repeated axenic re-cultivation. Prolonged treatments of P. indica cultures with various antibiotics could not completely eliminate the bacterium, though the number of detectable endobacteria decreased significantly, resulting in partial-cured P. indica (pcPiri). pcPiri showed reduced growth in axenic cultures and poor sporulation. Consistent with this, pcPiri also showed reduced plant growth promotion and reduced systemic resistance against powdery mildew infection as compared with riPiri and lcPiri. These results are consistent with the assumption that the endobacterium R. radiobacter improves P. indica’s fitness and thus contributes to the success of the tripartite Sebacinalean symbiosis.